Al-Sha‘bun al-Ṣūmālī bayna al-Faṣā’il al-Maslaḥah wa al-Ḥarakāt al-Islāmiyyah wa al-Ḥukūmah al-Intiqāliyah al-‘Ᾱjizah - ShÅ«rÄ«, â€˜Abduh â€˜Umar (Jurnal Usuluddin, 2002)
With the new phenomenological developments on the Muslim-Western relations, the selective interpretations given to the terrorist activities and its connection to the horn of Africa, as the United States establishes military base on the shorelines of this Muslim nation, the study of Somali political state-of-affairs becomes paramount to the academic community. As a Muslim nation ravaged by civil war, tribalism and avaricious warlords, Somalia remains a lesson for other nations who enjoy political stability and sustainable governance. This paper is a study of the current political situation and the future undertakings of Somalia. It presents and interprets the historico-social elements, such as irredentism, that has caused the infrastructural decadence of the Somali political system. While analyzing the aforementioned factors, the paper focuses on the causes of political upheavals and societal dismantlement. As the literature on this subject is extremely limited the paper contributes to the informational development to overcome this scarcity. Besides the paper highlights the role of the Muslim movements such as al-Itihad and al-Islah in the societal and political improvements during this arduous epoch.